Analysis of labeling and sodium content of olives in preserves sold in supermarkets in Teresina- PI (Research, Society and Development, 2023)
Food labeling establishes communication between producers and consumers, helping them with information about the product. The commercialization of canned foods such as olives is growing every day and with that the consumption of sodium used in conservation processes also increases. From this perspective, labeling has a very important impact on consumers, when presented correctly. Thus, the research aimed to evaluate the compliance of the general and nutritional labeling and the sodium content of preserved olives marketed in Teresina-PI. To verify compliance and non-compliance, checklists were prepared based on Brazilian legislation, and data statistics consisted of descriptive analysis performed in the Microsoft Excel program. 25 labels from 5 different brands were verified, divided into 6 categories, namely: green olive with pit (n=5), green olive without pit (n=5), sliced green olive (n=5), black olive with pit (n=3), pitted black olives (n=3), sliced black olives (n=4). An overall average of 94% compliance with legislation was found. Regarding the sodium content, the highest index presented 1,720mg and for the lowest index it presented 1,085mg. In this way, better inspection of products by Organs competent bodies is necessary and suggests that consumers consult the nutritional labeling to purchase products with lower levels of sodium.